The Effect of Food Intakes on Musculoskeletal Pains - Seyedeh Nasim Habibzadeh (Journal of Skeletal Muscle, 2020)
Some certain foods or drinks have specific effects on musculoskeletal frameworks in time of pain. For instance, the extra intake of salt declines muscular spams (or cramps) in different limbs. The regular consumptions of milk products reduce the upper or lower musculature weakness and pain. The hot drinks and foods as other examples can help to mitigate the abdominal pains. Indeed, warm drinks boost memory through lowering the pressures in different brain ‘sections (or lobs) in fatigue time. Some plant - based diets assist to the better digestion through faster and more smooth facilitation of food transformation in stomach areas. The plant – based dietary also can decline the heart muscle shocking impulse. However, some people for different reasons (i.e. cultural) do not consume some specific foods and drinks that can be kind of disadvantages for musculature system. Nonetheless, increasing the knowledge of daily food intakes can significantly help to improve musculoskeletal health in different individual in an uncertain condition.
Keywords: Food properties